Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/hyp.14616
|View full text |Cite
|
Sign up to set email alerts
|

Effects of single‐ and multi‐site calibration strategies on hydrological model performance and parameter sensitivity of large‐scale semi‐arid and semi‐humid watersheds

Abstract: In large‐scale watersheds, only the calibration of parameters for the outlet may ignore spatial heterogeneity and fail to meet the simulation accuracy of local areas. Based on the runoff observation data of three hydrological stations (Qingyang, Yangjiaping and Zhangjiashan) in the Jinghe River Watershed, single‐ and multi‐site calibration strategies were designed to investigate the performance and applicability of the Soil and Water Assessment Tool (SWAT) in predicting the monthly runoff of nested catchments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…In contrast, several other studies have found that performance was largely equivalent for multi-site and single-site calibration techniques (e.g., Franco et al, 2020;Lerat et al, 2012;Wu et al, 2022a).…”
Section: Introductionmentioning
confidence: 79%
“…In contrast, several other studies have found that performance was largely equivalent for multi-site and single-site calibration techniques (e.g., Franco et al, 2020;Lerat et al, 2012;Wu et al, 2022a).…”
Section: Introductionmentioning
confidence: 79%
“…A standard algorithm in SWAT-CUP called Sequential Uncertainty Fitting 2 (SUFI-2) was applied for multi-site model calibration and validation for monthly time steps [52,53] (Figure 3). SUFI-2 performs sensitivity analysis via global sensitivity analysis to test the sensitivity of model parameters, which is indicated by the t-stat and p-value [28,[54][55][56]. The parameter has greater sensitivity if it has a higher absolute t-stat value [28].…”
Section: Swat-cup Sensitivity Analysis Calibration and Validationmentioning
confidence: 99%
“…The R 2 value ranges from 0 to 1, where 0 indicates that the regression model explains none of the variance in the dependent variable, meaning it does not fit the data at all. A water balance model is deemed successful when it achieves a higher coefficient of determination R 2 , indicating a more favorable outcome [68]. R 2 is defined as follows [68,69]:…”
Section: Model Performance Criteriamentioning
confidence: 99%
“…A water balance model is deemed successful when it achieves a higher coefficient of determination R 2 , indicating a more favorable outcome [68]. R 2 is defined as follows [68,69]:…”
Section: Model Performance Criteriamentioning
confidence: 99%